Analisis Lingkungan Kerja Dan Kepemimpinan Direktur Terhadap Budaya Keselamatan Pasien RSGM IIK Bhakti Wiyata - Faisal Rizki; Sumarji Sumarji (Universitas Islam Kadiri, 2023)
Patient safety is a component of health facilities quality indicators. Implementing a patient safety culture has challenges. Implementation of safety culture is influenced by behavioral and environmental attitudes. Implementation patient safety in RSGM isn’t optimal, so it’s necessary to perform research: Effect of Environment and Leadership of Director on Patient Safety Culture in RSGM IIK Bhakta. Research is quantitative. Information obtained of numbers processed using SPSS statistical analysis. Multiple linear regression analysis technique with variables of environment, leadership, and patient safety culture. Hypothesis with T-test to determine the effect environment and leadership on patient safety culture. The results: environment and leadership had a positive and significant effect on patient safety culture. Results the regression coefficient (R) of 0.743 and coefficient of determination (R2) of 0.552. Results of F-test a significant level of 0,000 <0,05. Concluded, the environment and leadership Director simultaneously a positive and significant effect on patient safety culture in RSGM IIK Bhakta. It’s because a conducive work environment makes employees work optimally and the director leadership effectively influences and controls employees to achieve patient safety.